Analysis of Factors Affecting the Quality Achievement of Road Preservation Work on the Long Segment Scheme of National Roads in West Sumatra - Gusman, Gusman; Yossyafra, Yossyafra; Yosritzal, Yosritzal (ASTONJADRO, 2025)
The long segment road preservation scheme represents the government’s effort to achieve strategic objectives for well-maintained roads and standards across the segments. Initially, all national road maintenance programs were implemented through self-management by individual road segment managers or Project Implementation Units (PPK), utilizing a conventional contract system executed periodically and focusing solely on the primary works for the effective road length. Routine maintenance of functional lengths was conducted by service users through self-management. Currently, the long segment road preservation scheme is set to replace conventional/self-management contracts, with the expectation of addressing longstanding issues. However, in practice, the implementation of the long segment road preservation projects still encounters challenges, as evidenced by instances of project delays resulting in penalties, substandard construction quality, and overdue project completion. Therefore, this research aims to identify the variables influencing the quality achievement of the long segment road preservation scheme and to ascertain which factors have the most significant impact. Utilizing the Delphi method, we gathered experts with relevant expertise in national road preservation under the long segment scheme in West Sumatra and collected their opinions. Based on the results of our survey, the factors deemed most significant by the experts affecting the quality achievement of the long segment road preservation are material factors, followed by equipment factors, quality testing standards, labor factors, and finally, work method factors. Consequently, several aspects warrant attention in future long segment road preservation projects to ensure quality achievement, including: (1) Utilizing materials that meet quality requirements, (2) Ensuring the suitability of the heavy equipment used, (3) Conducting regular calibrations of the Asphalt Mixing Plant (AMP) and other quality testing equipment, (4) Enhancing labor skills through various training programs, and (5) Adjusting work methods to align with other quality standards.